Caregiver Characteristics and Barriers to Resource Use: Findings From a Rural State Caregiver Survey - Maija Reblin PhD; Nancy Gell PT, PhD, MPH; Kelly Melekis PhD; Christine M. Proulx (Gerontology and Geriatric Medicine, 2024)
Background: Despite the key role family caregivers play in the US healthcare system, they are not systematically identified and tracked, limiting our knowledge about this important group. Objective: Our objective was to identify caregiver characteristics and barriers to service delivery in a primarily rural state. Methods: As part of a quality improvement project, a cross-sectional online survey was fielded in clinical and community settings. Participants included 85 self-identified adult caregivers of another adult with an illness, condition, or disability from within a US state healthcare network. Descriptive analyses were conducted, and inferential statistics were used to compare urban versus rural respondents and older versus younger respondents. Results: Caregivers were responsible for a wide range of care activities and particularly older caregivers spent a significant amount of time providing care. Older caregivers also reported significantly lower levels of burden compared to younger caregivers, yet both groups had clinically high levels on average. Caregivers reported receiving helpful emotional support, but needed more tangible support and were limited by availability and cost. Conclusions: There is a need to fund comprehensive caregiver programing and address caregivers’ own social and physical health needs to reduce caregiver burden.